EXTRAPOLATING HEPATOCELLULAR CARCINOMA (HCC) RISK FROM AFLATOXIN EXPOSURE IN FOOD GRAINS AND LEGUMES USING DIETARY EXPOSURE RISK ASSESSMENT (DERA) CALCULATIONS (Jurnal Teknologi (Sciences & Engineering), 2025)
This study quantifies aflatoxins, which are linked to about 20% of cancer-related deaths globally, in food samples from open markets in Malaysia and Nigeria. Using optimized ultra-fast high-performance liquid chromatography (HPLC)aflatoxin levels were measured in 44 Malaysian and 84 Nigerian samples of peanuts, maize, wheat, and rice by matrix-matched calibration approach. Contamination was found in 40.9% of Malaysian samples, in the range of 8.68 – 77.4 ng/g, and in 64.3% of Nigerian samples, with levels between 0.21 and 114.4 ng/g. The Dietary Exposure Risk to Aflatoxins (DERA) was calculated, yielding a mean exposure of 11.2 – 25.1 ng/kgbw/day in Malaysia and 23.0 – 50.1 ng/kgbw/day in Nigeria. These exposure levels correspond to an estimated annual risk of HCC of 5.7 to 12.8 cases per 100,000 people in Malaysia and 26.6 to 57.9 cases per 100,000 in Nigeria. The margin of exposure (MOE) indicated a high risk of aflatoxin exposure and related cancer in these regions, suggesting an urgent need for stricter aflatoxin monitoring and regulations on non-packaged, locally produced grains.